ANALISIS USAHA HOME INDUSTRY KERUPUK PULI (STUDI KASUS DI DESA SARIROGO, KECAMATAN SIDOARJO, KOTA SIDOARJO) - Irfan Rosidi; Dewi Riza Lisvi Vahlevi (ICO EDUSHA, 2022)
Home industry puli crackers are one of the businesses found in Sarirogo Village, Sidoarjo District, Sidoarjo City. This business is a source of income for the people in the village, but sometimes business actors have difficulty in running the business. Objective: The purpose of this study is to analyze the condition of the puli cracker home industry business in Sarirogo Village, Sidoarjo District, Sidoarjo City, and identify the factors that affect the implementation of the business. Research Methods: The research method used in this study is a qualitative method with a case study approach. Data collected through interviews with puli cracker home industry business actors, direct observation at business locations, and documentation studies. Results and Discussion: The results showed that the puli cracker home industry business in Sarirogo Village, Sidoarjo District, Sidoarjo City experienced difficulties in terms of finances, capital, and raw materials. Factors influencing the implementation of the business include lack of access to information and lack of access to the market. Keywords: Home Industry Puli Crackers, Development Analysis, Family Value Analysis References Anoraga P, J. S. (2002). Koperasi, Kewirausahaan dan Usaha Kecil. (Jakarta : Rineka Cipta 2002), 244. Arikunto. (2010). Prosedur penelitian: Suatu Pendekatan Praktek. Jakarta: Rineka Cipta. Badan Pusat Statistik. (2001). Industri Kecil dan Kerajinan Rumah Tangga (IKKR). (Jakarta, 2001)., 4. Firmansyah, A. (2007). Pengaruh perubahan harga dan teknologi terhadap produksi dan penggunaan bahan baku di Perusahaan Kerupuk Ratna Sari, Tanggerang [skripsi]. Bogor: Fakultas Pertanian, Institut Pertanian Bogo, Bogor. Harimurti. (2012). Manajemen Usaha Kecil. Yogyakarta: BPFE. Judi Suharsono, Hosnol Wafa, Mustakim. (2017). Pengembangan Usaha Industri Kreatif Kerupuk Puli. Seminar Nasional & Call For Paper, FEB Unikama Peningkatan Ketahanan Ekonomi Nasional dalam Ranka Menghadapi Persaingan Global. Rangkuti. (2015). Analisis SWOT Teknik Membedah Kasus Bisnis. PT. Gramedia Pustaka Utama. Jakarta. Sugiyono. (2018). Metode Penelitian Kualitatif, 213. Suryana. (2006). Kewirausahaan Pedoman Praktis Kiat dan Proses Menuju Sukses. Jakarta: Salemba Empat. Tri wardani, Frida Dwi Anggraeni. (2018). Iptek Bagi Masyarakat Kelompok Usaha Kerupuk Puli di Desa Toyomarto, Kecamatan Singosari Kabupaten Malang. Jurnal Teknologi Pangan 9, no.1. Wahyono, M. (2006). Pembuatan Aneka Kerupuk. Jakarta: Penebar Swadaya.